CORPORATE SUSTAINABILITY REGIME OF PT. BERLIN PHARMA INDONESIA: ASSESSMENT OF COMPANY READINESS IN IMPLEMENTING SUSTAINABILITY GOALS USING BETTER-BUSINESS-SCAN (BBS) FRAMEWORK - Naulita, Puty
PT Berlin Pharma Indonesia is a medical subsidiary from Germany committed to achieving the 2030 sustainability goals, but the VUCA world makes that not easy. Many challenges can be called grand challenges because they affect large parts of society and require significant changes in behavior, technology and organizations to overcome. Some problems are complex and interconnected, often referred to as wicked problems because they are difficult to define and solve. For PT Berlin Pharma Indonesia, the issue of profitability is the company's current focus. Whether sustainability goals and profitability goals can be synergized, what are the challenges currently faced, how to optimize existing resources, and how the company's readiness to undergo these commitments is measured using the Better Business Scan framework. The Better Business Scan is an online tool designed by the Rotterdam School of Management in 2020 to map the sustainability transition phase a company is in and understand the challenges it poses. It can be a useful tool for managers who want to improve their sustainability performance as it measures the gap between sustainability intentions (business case) and realization (business model). The data is taken from the survey results and follow-up interviews of middle and upper management, the BBS analysis results show that the gap between intention and realization is relatively small, which may be caused by setting goals that are too easy. On the other hand, there is a gap between the sustainability goals set by the parent company and the subsidiaries. As a result, Berlin Pharma Indonesia can begin setting SDGs goals that are more challenging and aligned with the parent company's ambitions, nexus approach is used to link the internal resources and synergize the sustainability effects. In aligning sustainability goals and addressing profitability challenges, it is important for Berlin Pharma Indonesia to integrate the SDGs into their corporate strategy, embed them into decision-making processes, and foster a culture of sustainability throughout the organization. Berlin Pharma Indonesia needs to upgrade its existing Business Model to a Business Model Canvas+ to integrate sustainable and profit-based activities.